Numerical study on natural convection in inclined enclosures with non-uniform boundary conditions / Cheong Huey Tyng - Cheong, Huey Tyng (2013)

(untitled)
The understanding on the phenomena of fluid flow and heat transfer processes in enclo- sures is an important problem in many engineering and industrial applications. It has been a challenge to find an optimal heat transfer with numerous analyses and experiments. The geometry of the system, that is, size and inclination angle of the enclosure and bound- ary wall temperature can be the factors that provide the optimal heat transfer for various engineering applications. Hence, the effect of enclosure inclination and aspect ratio will be the subjects of the present study. A rectangular enclosure filled with fluid is consi- dered. Sinusoidal variation of temperature is applied on the left wall while the opposite wall is cooled with a constant temperature. The top and bottom walls of the enclosure are adiabatic. The enclosure inclination is an inclination angle bounded between the bottom wall and the horizontal plane. The gravity is acting in vertically downward direction. The flow is considered to be two-dimensional, Newtonian, incompressible and laminar. The fluid properties are constant and the Boussinesq approximation is valid for the density variations. The governing equations and boundary conditions are derived based on the physical model proposed. The governing system of partial differential equations are non- dimensionalized using the suitable dimensionless variables. This approach reduces the complexity in physical quantities for solving the system of partial differential equations. The finite difference method is used to discretize the set of partial differential equations. An appropriate numerical algorithm is developed to find the numerical solutions of heat transfer and fluid flow in the enclosures. The numerical results are validated with previ- ous studies. The results of the flow and temperature as well as the rate of heat transfer in enclosures are presented graphically. The flow structures and temperature distributions are affected by the enclosure inclination. The aspect ratio also affects the heat transfer in the enclosure.